Implementation Plan in Response to Board-Endorsed Recommendations Arising from the IEO Evaluation of IMF Interactions with Member Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper presents a forward-looking implementation plan for Board-endorsed recommendations of the IEO Evaluation of IMF Interactions with Member Countries. Executive Directors welcomed the important insights offered into the effectiveness of these interactions, which are key to the Fund's ability to achieve its goals. They broadly supported the need to enhance the traction of Fund surveillance, improve the effectiveness of outreach, and strengthen the management of interactions. Directors, nonetheless, 'observed that the report covers principally the pre-crisis period, and significant progress has been made on several fronts since then.' In drawing up the implementation plan, this note focuses on points commanding broad support by the Executive Board, and builds on existing plans and ongoing reform initiatives that are broadly aligned with the evaluation's recommendations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Director; Management; PP; Staff; The Fund; United Kingdom